1959
DOI: 10.1113/jphysiol.1959.sp006175
|View full text |Cite
|
Sign up to set email alerts
|

The release of 5‐hydroxytryptamine in relation to pressure exerted on the intestinal mucosa

Abstract: In a recent investigation (Biilbring & Lin, 1958) it was found that small amounts of 5-hydroxytryptamine (5-HT) were continuously released into the lumen of an isolated loop of intestine. The quantity released was directly related to the height of intraluminal pressure. Experiments carried out to ascertain whether 5-HT was liberated as a result of pressure on the mucosa, or as a result of peristaltic activity which was evoked by raising the pressure, were not entirely conclusive. When peristaltic activity was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
115
0

Year Published

1962
1962
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 275 publications
(122 citation statements)
references
References 1 publication
4
115
0
Order By: Relevance
“…This observation is in marked contrast to the effects of granisetron or ICS 205-930 and conflicts with the potent ability of this compound to antagonize the Bezold-Jarisch reflex in anaesthetized rats (ID50 against 2-methyl-5-HT = 0.4pgkg-, i.v., Butler et al, 1988; ID50 against 5-HT = 3.6,ugkg-1, i.v., Sanger, 1990) (Sanger & Nelson, 1988). If granisetron and ICS 205-930 act by antagonizing a 5-HT receptor, this may be present on the peripheral afferent nerve fibres, being activated by 5-HT released from enterochromaffin cells by distension (Bulbring & Crema, 1959). Alternatively, they may also act within the central nervous system or spinal cord.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This observation is in marked contrast to the effects of granisetron or ICS 205-930 and conflicts with the potent ability of this compound to antagonize the Bezold-Jarisch reflex in anaesthetized rats (ID50 against 2-methyl-5-HT = 0.4pgkg-, i.v., Butler et al, 1988; ID50 against 5-HT = 3.6,ugkg-1, i.v., Sanger, 1990) (Sanger & Nelson, 1988). If granisetron and ICS 205-930 act by antagonizing a 5-HT receptor, this may be present on the peripheral afferent nerve fibres, being activated by 5-HT released from enterochromaffin cells by distension (Bulbring & Crema, 1959). Alternatively, they may also act within the central nervous system or spinal cord.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that 5-hydroxytryptamine (5-HT) can be released by increasing the intraluminal pressure of the small intestine (Bulbring & Crema, 1959;Burks & Long, 1966). A potential role of endogenous 5-HT in modulating distension-induced reflexes was therefore examined by use of the selective 5-HT3 receptor antagonists granisetron (BRL 43694;Sanger & Nelson, 1989), (Richardson et al, 1985) and ondansetron (GR 38032F; Butler et al, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…Mechanical distension of the intestinal mucosa and a variety of neurohormonal stimuli have been shown to release 5-HT from the EC cells mainly into the interstitial space (3), but also into the gut lumen (4, 5). The released 5-HT binds various subtypes of 5-HT receptors on enteric neurons, smooth muscle cells, and epithelial cells and regulates intestinal fluid transport and peristalsis (2,4,6).In the pancreas, 5-HT is mainly present in β cells of the islet of Langerhans (7,8) and in serotonergic pancreatic nerve fibers (2, 9). The presence of the EC cells in the exocrine pancreas has also been noticed but their exact localization and function have not been described (8).…”
mentioning
confidence: 99%
“…The mechanism of luminal release of 5HT has been studied more extensively in the adult animals but scarcely in the developing animals. In adult animals, the luminal release of 5HT is affected by various stimuli such as cholinergic or adrenergic mechanism [1,2] or high intraluminal pressure [4]. However the functional significance of luminally released 5HT is only poorly understood.…”
mentioning
confidence: 99%